AKURASI HISAB AWAL BULAN QAMARIYAH DALAM KITAB KHULASHAH AL-WAFIYAH & EPHEMERIS - Fika Andriana, Asmuni, Watni Marpaung (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2017)
This research aims to analyze deeply about: 1) The method of determining the beginning of qamariyah month according to the book of Khulashah al-Wafiyah, 2) The method of determining the beginning of qamariyah month according Ephemeris, 3) Hisab accuracy level in determining the beginning of qamariyah month according to the book of Khulashah al-Wafiyah and Ephemeris. This research is a library research in the form of qualitative descriptive- analytical research. The primary data source are the Khulashah al-Wafiyah and The Ephemeris, while secondary data obtained through the study of various related literature. Then the data is analyzed by content analysis. The results showed that the method of determining the beginning of qamariyah month according to Khulashah al-Wafiyah book in advance through calculation taqribi with reference to the data in the table that is already provided at the end of the book. Based on the calculation of the intrinsic taqribi followed by calculation five correction to the moon’s data. When applied to the hisab of the beginning of Shawwal 1437 H / 2016 M, the results show that hilal’s high negative or position of the moon is still below the horizon. This according with the facts that occurred on the ground when it was that the height of the new moon is still negative so that the Ramadhan in istikmal right to 30 days. Similarly, the results of the hisab of Syawwal 1437 H according to Ephemeris which also showed negative height of the new moon. Thus, the accuracy in determining the beginning of the month of qamariyah according to the book of al-Wafiyah Khulashah classified as already a high degree of accuracy that can even match the real of contemporary hisab.